The Role of Deubiquitinating Enzymes in the Various Forms of Autophagy - Csizmadia, Tamás (Int J Mol Sci, 2020)
Deubiquitinating enzymes (DUBs) have an essential role in several cell biological processes via removing the various ubiquitin patterns as posttranslational modification forms from the target proteins. These enzymes also contribute to the normal cytoplasmic ubiquitin pool during the recycling of this molecule. Autophagy, a summary name of the lysosome dependent self-degradative processes, is necessary for maintaining normal cellular homeostatic equilibrium. Numerous forms of autophagy are known depending on how the cellular self-material is delivered into the lysosomal lumen. In this review we focus on the colorful role of DUBs in autophagic processes and discuss the mechanistic contribution of these molecules to normal cellular homeostasis via the possible regulation forms of autophagic mechanisms.